Secured Multi Owner Data Sharing in Cloud Using AES Algorithm - Praveen, N.; Manohar, P. Satya Sai; Kumar, M. V. Praveen (International Journal of Psychosocial Rehabilitation, 2020)
Cloud Computing enables us to easily store data and simply share data with others. Due to the safety threats in any cloud, users take measures to secure their data, such as signatures, on their data to protect the integrity. With the advent of cloud computing, it becomes increasingly popular for the data owners while allowing the data users to retrieve these data. For privacy concerns, over encrypted cloud data, several researches under the single owner model have been done. However, most cloud servers which are in practice do not just serve one owner, instead, they support multiple owners to share the benefits brought by the servers. In our project we proposed a multiple owner file sharing system in cloud computing, here the user can use their particular owner file and also he can access other owner files. For accessing, the way of request and response is used. If another owner responds the user, it means that he can get the private key from the owner and then he can access the files.